Angiotensin Converting Enzyme 2 (ACE2) in Pregnancy: Preeclampsia and Small for Gestational Age - Tamanna, Sonia; Clifton, Vicki L.; Rae, Kym; van Helden, Dirk F.; Lumbers, Eugenie R.; Pringle, Kirsty G. (Frontiers in Physiology, 2020)
Introduction: An imbalance in angiotensin (Ang) peptides could contribute to the pathophysiology of preeclampsia (PE) and poor fetal growth. Methods: We measured maternal plasma levels of Ang peptides and converting enzymes in non-pregnant women (n=10), in normal pregnant women (n=59), women delivering small for gestational age babies (SGA, n=25) across gestation (13-36 weeks) and in women with PE (n=14) in their third trimester. Results: Plasma ACE, ACE2 and Ang-(1-7) levels, and ACE2 activity were significantly higher throughout gestation in normal pregnant women compared with non-pregnant women; neprilysin (NEP) levels were not changed. In SGA pregnancies, levels of NEP, Ang-(1-7), and ACE2 activity were the same but ACE and ACE2 levels were higher than in normal pregnant women. In women with PE, plasma ACE, ACE2, NEP and Ang-(1-7) levels and ACE2 activity were lower than levels measured in normal pregnant women. Conclusion: The higher plasma ACE2 levels and activity in pregnancy could be responsible for the higher Ang-(1-7) levels, as an alternative pathway via NEP was not affected by pregnancy. In women with PE, there were lower levels of both ACE2 and NEP, which might contribute to the known reduction in Ang-(1-7) levels in PE. The ACE2 - Ang-(1-7) pathway is both vasodilator and anti-inflammatory. Since soluble ACE2 has been reported to prevent binding of the novel coronavirus, SARS-CoV-2, to membrane bound ACE2, the interplay between ACE2 and the coronavirus and its impact in pregnancy requires further investigation.